PENGARUH VICTIMBLAMING (PENYALAHAN KORBAN) TINDAK PIDANAPORNOGRAFI BALAS DENDAM TERHADAP PROSES PENEGAKAN HUKUM DALAM SISTEM PERADILAN DI INDONESIA - Deby Rahmatul Fitri; Erdianto Erdianto; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Revenge pornography is an act of pornography by utilizing the possession of pornographic material that is legally obtained but disseminated with the aim of revenge. The purpose of the perpetrator is not only to spread pornographic photos but to get back the hurt he has experienced. Revenge pornography is potentially even more dangerous and lasting than real-life harassment. In this writing the author focuses on women as victims who in practice, the influence of victimblaming is still more dominant than the victim perspective approach and the victim's mental recovery. The purposes of writing this thesis are: first, to determine the extent of victimblaming's influence on victims of revenge pornography in the law enforcement process in the Indonesian judicial system. Second, to find out how ideal the protection of victims of revenge pornography crime who has experienced victimblaming in the justice system in Indonesia.The author conducts research using the normative juridical method or literature study in order to obtain secondary data through documentary studies, namely by studying and analyzing comparatively descriptive of the laws and regulations with theories that have a relationship to the problems studied. From the research results, there are two main things that can be concluded: First, the effect of victimblaming on victims of revenge pornography crime in the law enforcement process is that so far, revenge porn has mostly occurred in the context of blaming the victim, negative reactions that have emerged have made victims reluctant to report their cases and cause absence of law enforcement processes. Second, ideally the protection of victims of revenge pornography by prioritizing the mental recovery of the victim.Keywords: effect - victim - victimblaming - revenge porn - protection